Correlation analysis between biomechanical characteristics of taekwondo double roundhouse kick and effective scoring of electronic body protector - Jia, Mengyao; Liu, Lin; Huang, Ruifeng; Ma, Yong; Lin, Shijie; Peng, Qian; Xiong, Jun; Wang, Zhaoyi; Zheng, Weitao (Frontiers in Physiology, 2024)
Objective: To explore the inherent relationship between lower limb biomechanical indicators and effective scoring values of double roundhouse kick (DRK) by taekwondo athletes, and to find key biomechanical factors that trigger effective scoring. Methods: Using the DAEDO Protector and Scoring System (PSS) in conjunction with the Vicon optical motion capture system and Kistler 3D force plate, kinematic and dynamic indicators of the front kicking motion were obtained from 12 professional taekwondo athletes (18.00±2.20 years, 182.15±8.62 cm and 70.00±14.82 kg). The correlation between kinematics, dynamics, and scoring values was initially analyzed using bivariate linear correlation.Subsequently, based on the results of the linear correlation analysis, a stepwise regression analysis was performed to establish a stepwise regression equation. Results: the results reveal that during the First Hit, there is a significant positive correlation (r>0, p<0.05) between peak hip flexion angular velocity of the dominant leg, knee abduction angle, and peak foot horizontal plane linear velocity of the non-dominant leg with effective score. On the other hand, peak ankle flexion angular velocity of the non-dominant leg, peak foot sagittal plane linear velocity, peak hip abduction angle, and peak hip flexion angle of the dominant leg exhibit a significant negative correlation (r<0, p<0.05) with effective score. These correlations hold statistical significance (DW>1.023). During the Second Hit, there is a significant positive correlation (r>0, p<0.05) between peak ankle internal rotation angular velocity of the dominant leg, foot coronal plane linear velocity, hip adduction angular velocity, and peak ankle internal rotation moment of the non-dominant leg with effective score. Conversely, peak hip flexion angle of the dominant leg shows a significant negative correlation (r<0, p<0.05) with effective score. All these variables have a statistically significant impact on effective score (DW>1.023). Conclusion: Explosive power, body posture, adequate terminal velocity, and body rotation have an association with effective scoring of the electronic protector. The peak angular velocity of the ankle joint of the dominant leg and the peak linear velocity of the foot horizontal plane of the non-dominant leg significantly contribute to the effectiveness score of the electronic protector.